Flemish Expressions : Representational Painting in the Twentieth Century - Schimmel, Paul; van Leuven, Hilde; Museum of Art, Fort Landerdale (Newport Beach : Newport Harbor Art Museum, 1986)
Ensor, James ; Khnopff, Fernand ; Smits, Jakob ; de Saedeleer, Valerius ; Spilliaert, Leon ; Servaes, Albert ; Gustave Van de Woestyne ; Wouters, Rik ; Permeke, Constant ; De Smet, Gust ; Van den Berghe, Frits ; etc.
Flemish Expressions : Representational Painting in the Twentieth Century, Newport Harbor Art Museum, Newport Beach, December 12, 1986 - February 22, 1987 ; Museum of Art, Fort Landerdale, Florida, March 12 - May 25, 1987
boek
Keywords: Vlaanderen